Penerapan Metode Diskusi dan Studi Kasus dalam Pembelajaran Fikih di MAN 1 Balangan - Ubaidillah Ubaidillah (STIT Syekh Muhammad Nafis Tabalong, 2025)
Fiqh learning in Islamic schools is often dominated by lectures, which leaves students passive and less actively involved in the learning process. However, fiqh material requires in-depth understanding and critical and analytical thinking skills. This study focuses on the application of discussion and case study methods in fiqh learning at MAN 1 Balangan, with the aim of determining how these methods influence students' activeness in expressing opinions, their ability to listen and respond to peers' arguments, and their involvement in collaborative problem-solving. This study used a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews with fiqh teachers and students, and documentation during the learning process. The results showed that discussion and case study methods were able to increase active student participation, foster courage in expressing opinions, and develop the ability to listen critically and respond to arguments constructively. In addition, students demonstrated high engagement in group work to solve fiqh problems, reflecting the development of collaborative skills and understanding of Islamic law. Although there were still obstacles such as unequal student participation and time constraints, the application of these methods was generally proven effective and relevant to the principle of deliberation in Islam and the demands of 21st-century learning. Therefore, it is recommended that discussion and case study methods be further developed in Islamic jurisprudence (fiqh) learning in madrasas.